DESKRIPSI PENENTUAN AWALN BULAN KAMARIAH MENURUT PANDANGAN AL-IRSYAD AL-ISLMIYAH - Prameswari, Zavitri Galuh (ELFALAKY: Jurnal Ilmu Falak, 2021)
Regarding the differences in the determination of the beginning of the month of Qamariyah there is no exception for several community organizations in Indonesia. One of them Al-Irsyad Al-Islamiyah community organization. According to exusting sources the organization of the community uses rukyatul hilal, but on the other hand it also uses hisab. After finding the two, the decision making process is still waiting for the government. The Al-Irsyad Al-Islamiyah community organization complies with government decisions, although in its organization there is a decree but it is only temporary. The government is a certainly mediator and does not take sides or corner existing comuunity organizations. It‟s just that there is a decision of the best definite government and has missed observations also calculations which are expected to be aceepted and can embrace all social organizations in Indonesia. Keywords : Al-Irsyad Al-Islamiyah, Rukyatul Hilal and Hisab